KEANEKARAGAMAN TUMBUHAN HERBAL DI PERKEBUNAN LAMBANAPU KABUPATEN SUMBA TIMUR - Jelita M.R. Kalli; Netri R. Sida; Kartini R. Ndai; Yesti R.Y. Danga; Ferdi U.H. Hamataka; Yubinanto Konda Meha; Anita Tamu Ina (FKIP Universitas Tanjungpura, 2022)
Herbal medicinal plants are plants that can be used as medicine, either intentionally planted or growing wild. The benefits of herbal plants among the community to be mixed and served as medicine to cure diseases, perform certain biological functions with many benefits that can be obtained from herbal plants by utilizing plantation land as land to grow herbal plants. The purpose of this study was to determine the types of herbal plants in the Lambanapu plantation area, East Sumba Regency. This research was carried out on Monday, April 25, 2022, which is located in the front of the Lambanapu plantation at SMP N. 1 Kambera, East Sumba Regency. The method used is the path/transect method with an observation plot measuring 6.25 x 3.75 m. Environmental factors are also measured including air temperature, soil pH and humidity. The results showed that the most dominant herbal plants in the lambanapu plantation were red spinach and kates mas.